Методологічні проблеми демократизації суспільства країн центрально-східної Європи - Головченко, А. В.; Головченко, А. В.; Golovchenko, A. (My University, 2012)
In presented article the was aspiring to deﬁ ne the essences of democracy, main theoretical and methodic approaches, structure and possibility of successful realisation of the society democratization basic prerequisites of countries in the Central-East Europe. Many theoretical basics of russian and foreign scientists were examined. s a consequence the author deﬁ nes two main approaches to understanding the prerequisites of democratization: structural and procedural approaches. Main types of structural prerequisites of democratization were deﬁ ned. The important role of separate political players is emphasized in the article in process or regress of democratic processes.
Головченко А. В. Методологічні проблеми демократизації суспільства країн центрально-східної Європи / А. В. Головченко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2012. – Вип. 45. – С. 203-215.
Keywords: методологічні проблеми суспільства; демократизація суспільства країн; центрально-східна Європа; методологические проблемы общества; демократизация общества стран; центрально-восточная Европа; methodological problems of society; democratization of society; Central and Eastern Europe